An alternative evaluation: online puzzle as a course-end activity - Genc, Zulfu; Aydemir, Emrah (Emerald Group Publishing Ltd, 2015)
Purpose - The purpose of this study is to determine whether the use of online puzzles in the instructional process has an effect on student achievement and learning retention. This study examined students' perception and experiences on use of puzzle as an alternative evaluation tool. To achieve this aim, the following hypotheses were tested: using puzzle activities in lessons increases student achievement, using puzzle activities in lessons increases retention of information learned by the students and students have positive attitudes toward using puzzle activities in lessons. This study uses an online puzzle system (OPS) by which instructors can prepare puzzle activities for students to solve online. The technical and functional properties of the OPS developed and used are beyond the scope of this study. Design/methodology/approach - A pre- and post-test with control group experimental research design was implemented. Study participants were tenth-grade students in the Information Technologies Department of Gazi Anatolia Technical and Industrial Vocational School in Elazig during the 2011-2012 year. Thirty students each were chosen for the experimental and control groups, totaling 60 students. During the study, a traditional instruction method was used for the control group, while the experimental group received both traditional instruction and performed activities using the OPS. The subject Fundamentals of Networking was chosen, and the implementation period lasted six weeks. Four weeks after completion of the study, the achievement level of students was calculated again to test learning retention. Findings - The first hypothesis of the study is, Using puzzle activities in the lessons increases the achievement of the students. In the teaching of the Networking Fundamentals Module of Information Technologies Course for tenth graders, a significant difference in favor of the experimental group was seen, where online puzzle activities were used in terms of student achievement. The second hypothesis of the study is, Using puzzle activities in the lessons increase the retention of the information learned by the students. Four weeks after completion of the study, the achievement levels of the students were calculated again to test learning retention. The learning retention of the students in the experimental group is higher than that of the students in the control group. In addition, students in the experimental group had positive attitudes toward online puzzle activities. Doing online puzzle activities accelerates learning for students and helps them learn networking terms by creating an enjoyable environment. Research limitations/implications - The current study was limited to six weeks of implementation during the 2011-2012 school year at Gazi Anatolia Technical and Industrial Vocational High School in Elazig. Similar studies could be conducted in other schools for longer periods and at different levels, so the findings can be compared with those of the current study. This study is further limited to an Information Technologies Course. Studies can be conducted with various courses using appropriate online puzzle activities. Puzzle types other than the crossword used in the OPS of the current study should be developed and added. The system should also be developed by visual multimedia objects, allowing it to be more interactive. Moreover, in the development process of such an OPS, educators, software designers, psychologists and scholars from other fields should work together. Usability tests should be conducted to improve user-friendliness of the system by adding various features related to functionality and visuality. Practical implications - From the findings of the study, it can be concluded that online puzzle activities help students understand subjects better and aid in exam preparation. Moreover, these activities are effective for students in terms of increasing understanding and retention of learned terms in and outside class, forming valuable learning experiences. Doing online puzzle activities in class as a course-end activity can be said to be more effective in students' learning than doing them outside of class. Crossword puzzles offer opportunities for students to accelerate learning by quickly mastering new words and phrases and by directing students to more actively interact with computer-related vocabulary and terminology as compared with the rote learning method. Originality/value - Paper-based puzzles are frequently used, and there are few Web-based puzzles. Despite their frequent use, preparing and evaluating paper-based puzzles can require a significant time investment; another disadvantage is the lack of immediate feedback. Based on the literature review, there is no dynamic OPS used for educational purposes. This study uses an OPS by which instructors can prepare puzzle activities for students to solve online. The originality of this study is OPS features and puzzle generation mechanism. The system presents a user-friendly interface with Turkish character (or any language) support and number-writing properties.
Keywords: Computer software; Teaching methods; Assessment; Online applications; Learning methods